Analisis Efektivitas Biaya (Cost Effectiveness Analysis) Penggunaan Antibiotik Seftriakson Dan Sefotaksim Pada Pasien Infeksi Saluran Kemih Di Rsd Dr. A. Dadi Tjokrodipo Bandar Lampung - Koernia Wahidah, Lilik; Tri Wahyuni, Novita; Andinni, Aulia (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2023)
Cost-effectiveness analysis is defined as an analysis to identify, measure and compare significant costs and their consequences of alternative interventions. Antibiotics are a group of drugs most often used to treat infectious diseases. Ceftriaxone and cefotaxime are the main options for treating UTI. Urinary Tract Infection (UTI) is a disease with conditions where there are very large numbers of microorganisms in the urine and can cause infection in the urinary tract. This study was designed to analyze the cost-effectiveness of ceftriaxone and cefotaxime treatment for inpatient urinary tract infections at dr. A. Dadi Tjokrodipo. The method used is descriptive with a retrospective pharmacoeconomic analysis approach. The sampling technique was purposive sampling and sampling 92 patient. The research results show characteristics based on sex most are female as much as 55 (60%), based on age ≥56 years in 35 patients (38%), and the highest length of hospitalization was 3 days in 45 patients (49%). The most widely used profile of antibiotic drug use in patients with urinary tract infections was cefotaxime with a total of 64 patients (70%). The average cost for each type of drug therapy from ceftriaxone is 735,117 and sefotaxime is 742,178. Ceftriaxone has the highest percentage of therapeutic effectiveness at 86% compared to cefotaxime at 71%. Antibiotics that are more cost effective are ceftriaxone compared to cefotaxime with an ACER calculation of 78.455. Keywords: Cost Effectiveness Analysis, Urinary Tract Infections, Ceftriaxone, Cefotaxime